2021
DOI: 10.1126/sciadv.abg4081
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors increase T cell immunity during SARS-CoV-2 infection

Abstract: The COVID-19 pandemic has spread worldwide, yet the role of antiviral T cell immunity during infection and the contribution of immune checkpoints remain unclear. By prospectively following a cohort of 292 patients with melanoma, half of which treated with immune checkpoint inhibitors (ICIs), we identified 15 patients with acute or convalescent COVID-19 and investigated their transcriptomic, proteomic, and cellular profiles. We found that ICI treatment was not associated with severe COVID-19 and did not alter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 55 publications
(67 reference statements)
2
19
0
1
Order By: Relevance
“…Patients who have recovered from SARS-CoV-2 presumably acquire cellular immunity to various viral antigens, while the vaccine creates immunity only against the spike protein, which may be the reason for the significantly reduced reinfection rate in patients who have recovered from SARS-CoV-2. However, we could not confirm or dismiss this presumption, as we did not test the immune response to other viral antigens [ 27 , 28 , 29 , 30 ]. Due to the importance of T-cell immunity, the development of a new vaccine that will primarily stimulate cellular immunity has begun.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have recovered from SARS-CoV-2 presumably acquire cellular immunity to various viral antigens, while the vaccine creates immunity only against the spike protein, which may be the reason for the significantly reduced reinfection rate in patients who have recovered from SARS-CoV-2. However, we could not confirm or dismiss this presumption, as we did not test the immune response to other viral antigens [ 27 , 28 , 29 , 30 ]. Due to the importance of T-cell immunity, the development of a new vaccine that will primarily stimulate cellular immunity has begun.…”
Section: Discussionmentioning
confidence: 99%
“…Such concerns have prompted some physicians and patients to discontinue anti-PD-1 therapy during anti-COVID-19 vaccination. Although studies have shown that anti-COVID-19 vaccination in patients with cancer is safe 13 and because ICI treatment does not increase the severity of COVID-19 infection, 14 until now, little data existed regarding the implications of anti-COVID-19 vaccination on the safety and efficacy of PD-1 inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the beneficial effects of an improved CD8 T-cell response may outweigh any minimal enhancement in immunopathology. Indeed, a recent study reported that immune checkpoint inhibitors can increase the T cell response in SARS-CoV-2 infected melanoma patients, without interfering with early interferon induction or aggravating inflammation [112].…”
Section: Plos Pathogensmentioning
confidence: 99%